Ultra culture-ultra reality: a content analysis of YouTube depictions of ultra endurance sport and comparisons to scientific literature - Colangelo, Jill; Smith, Alexander; Buadze, Ana; Liebrenz, Michael (Frontiers in Sports and Active Living, 2023)
Introduction Interest in ultra endurance sport (UES) is increasing, with relevant events growing in popularity. However, these activities may encompass more complex characteristics and demands that do not correspond to scientifically validated correlations between physical activity and improved health. It is unknown whether high volume training for UES can have adverse implications, although certain sociocultural aspects of western society, such as an emphasis on autonomy and self-directed success, may encourage participation as a representation of personal achievement. As media depictions of UES can be highly influential, we aimed to explore prominent messages to better comprehend the values and aspirations of established and aspiring ultra endurance athletes (UEA). Methods Using qualitative, conventional content analysis techniques, we evaluated n = 15 popular YouTube videos on various UES to synthesize the most common themes. A YouTube search was conducted, and videos were selected based on sport and relevance. Subsequently, videos were analyzed and coded to discern the most frequently repeated themes. Results Five recurring themes were identified: discussion of the mental aspects of UES participation; the adoption of folk-tale storytelling; dietary habits of UEA; a focus on pain and suffering; the use of words associated with mental illness as a colloquial descriptor of UES/UEA. Discussion YouTube depictions of UES participation appear to accentuate suffering and co-occurring phenomena as attractive qualities. These resonate with sociocultural ideologies in western contexts, which emphasize fitness and personal success, but appear inconsistent with evidence around potentially adverse health-related implications of UES. Conclusion Discrepancies between popular portrayals of UES and scientific evidence suggest a need for greater community education and information sharing about sport-specific risk factors for physical and mental health conditions and appropriate training protocols. Further research is also required to better define the relationship between motivations for UES participation and overall health using interdisciplinary approaches.